1x2+2x3+3x4+4x5+...+9x10
Răspunsuri la întrebare
Răspuns de
2
n = 9
1*2 + 2*3 + 3*4 + ...+ n*(n+1) = n(n+1)(n+2) : 3 prin formulă.
1*2 + 2*3 + 3*4 + ...+ 9*10 = 9(9+1)(9+2) : 3 =>
1*2 + 2*3 + 3*4 + ...+ 9*10 = 9*10*11 : 3 =>
1*2 + 2*3 + 3*4 + ...+ 9*10 = 9*110:3 =>
1*2 + 2*3 + 3*4 + ...+ 9*10 = 3*110 = 330
1*2 + 2*3 + 3*4 + ...+ n*(n+1) = n(n+1)(n+2) : 3 prin formulă.
1*2 + 2*3 + 3*4 + ...+ 9*10 = 9(9+1)(9+2) : 3 =>
1*2 + 2*3 + 3*4 + ...+ 9*10 = 9*10*11 : 3 =>
1*2 + 2*3 + 3*4 + ...+ 9*10 = 9*110:3 =>
1*2 + 2*3 + 3*4 + ...+ 9*10 = 3*110 = 330
Alte întrebări interesante